1994
DOI: 10.1093/mnras/271.3.719
|View full text |Cite
|
Sign up to set email alerts
|

The principle of least action and clustering in cosmology

Abstract: A scheme is developed which enables one to trace backwards in time the cosmic density and velocity elds, and to determine accurately the current-epoch velocity eld from the current-epoch density eld, or vice versa. The scheme implements the idea of Giavalisco et al. (1993) that the principle of least action should be used to formulate gravitational instability as a two-point boundary-value problem. We argue that the Eulerian formulation of the problem is to be preferred to the Lagrangian one, on grounds of com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…This principle was used together with the assumption that the initial peculiar velocities of galaxies are zero in order to predict galaxy orbits in the local group (Peebles 1989) and for galaxies within 3000 kms 1 (Shaya, Peebles and Tully 1995). Giavalisco (1993) and Susperregi and Binney (1994) also use least action in the context of an evolving mass distribution, in the latter case applied to mass smoothed onto an Eulerian grid.…”
Section: Introductionmentioning
confidence: 99%
“…This principle was used together with the assumption that the initial peculiar velocities of galaxies are zero in order to predict galaxy orbits in the local group (Peebles 1989) and for galaxies within 3000 kms 1 (Shaya, Peebles and Tully 1995). Giavalisco (1993) and Susperregi and Binney (1994) also use least action in the context of an evolving mass distribution, in the latter case applied to mass smoothed onto an Eulerian grid.…”
Section: Introductionmentioning
confidence: 99%
“…• if α = 0 then Q has a real double root η 1 = η 2 and a simple one η 3 . The related instantaneous kinematic shows a planar-axial symmetry (either a contraction within a plane with an expansion toward a transverse direction or vice versa), see Sect.…”
Section: Evolution Of Functions β N=23mentioning
confidence: 99%
“…Later on, least action methods [2] were also used in reconstruction procedures with more reliable estimates, see e.g. [3][4][5][6][7]. Both approaches assume that the peculiar velocity field decomposes into a "divergent" component due to density fluctuations inside the surveyed volume, and a tidal (shear) component, consisting of a bulk velocity and higher moments, due to the matter distribution outside the surveyed volume [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cosmological reconstruction should, however, take advantage of our knowledge that the initial mass distribution was quasi‐uniform at baryon–photon decoupling, about 14 billion years ago (see, e.g., Susperregi & Binney 1994). In a recent Letter to Nature (Frisch et al 2002), four of us have shown that, with suitable assumptions, this a priori knowledge of the initial density field makes reconstruction a well‐posed instance of what is called the optimal mass transportation problem.…”
Section: Introductionmentioning
confidence: 99%